Kajian Distribusi Konsentrasi Sedimen Suspensi Menggunakan TSS Meter pada Sungai Brantas di Desa Pendem Kota Batu - Wiryamanta, Dhimas Raditya; Sumiadi, Sumiadi; Dermawan, Very (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
The river is the site of sedimentation, which sediment is sourced from erosion and erosion of the soil layer on the slopes of the river. This sedimentation can decrease water utilization because it results in reduced capacity and water quality in rivers, irrigation channels, reservoirs, and others. So research is needed to find out the distribution of suspension sediment concentrations to plan the steps in the management of water along the river. The method used in solving this problem is to use portable TSS Meter, Partech 740 structure to facilitate the collection of the concentration of suspension sediment in the field easily at any given height. This study was conducted ten (10) times sampled at different times and days using portable TSS Meter aids to determine the distribution value of suspension sediment concentration at each flow depth. In this study, there is a relationship between flow discharge (Qw) and suspension sediment discharge (Qs) with the equation Qs = 1.1071.Qw2.3488, and there is a relationship between flow discharge and the average suspension sediment concentration with the equation C =Â 12.813.Qw1.3488, and the last obtained magnitude of rouse exponent factor is in the range of 0.01435 â€“ 0.054064.